Developing Collaborative Communication Skills: A Role-play Approach for University Students - Salainti, Engelina (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
Speaking is one of the most crucial language skills for students. It allows them to communicate their ideas and thoughts clearly and effectively, participate in class discussions and activities, build relationships with classmates and teachers, and succeed in their studies. Several factors influence students to speak English, they struggle with the fear of making grammatical mistakes, limited vocabulary, and lack confidence. This study investigates students' opinions on the role-playing approach in developing their collaborative communication skills, and how the role-playing technique improves students' speaking ability. This study used questionnaires, and data was analyzed with Likert Scale. The result showed that most of the students agreed that the Role-Playing approach develops their communication skills, while fewer students were neutral.